2018
DOI: 10.18821/0016-9900-2018-97-1-16-20
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Environment and Risk to Health of the Population Residing Under the Exposure to Emissions From Colored Metallurgy Enterprises and Wood Processing Industry

Abstract: In the residential area under the impact of emissions from non-ferrous metallurgy and woodworking industry, the quality of atmospheric air was shown to fail to meet the requirements of hygienic standards for the content of suspended solids in air [≤ 4 MPC for maximal single dose (MPCmsd), ≤ 12.5 MPC for average daily dose (MPCadd), phenol (≤ 5.6 MPCmsd, ≤ 4.83 MPCadd), formaldehyde (≤ 1.56 MPCmsd, ≤ 6.58 MPCadd), fluoride gaseous compounds (≤ 3.75 MPCmsd, ≤ 12.4 MPCadd), etc. The quality of potable water in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Идея создания и распространения практики «Здоровых городов» предполагает пересмотр основных принципов охраны здоровья на урбанизированных территориях. Новые политики взаимодействия всех ветвей власти и гражданского общества, реорганизация системы здравоохранения, участие населения в решении вопросов здоровья и окружающей среды не снимают проблемы развития промышленных и транспортных объектов города [10,14,16].…”
Section: Introductionunclassified
“…Идея создания и распространения практики «Здоровых городов» предполагает пересмотр основных принципов охраны здоровья на урбанизированных территориях. Новые политики взаимодействия всех ветвей власти и гражданского общества, реорганизация системы здравоохранения, участие населения в решении вопросов здоровья и окружающей среды не снимают проблемы развития промышленных и транспортных объектов города [10,14,16].…”
Section: Introductionunclassified
“…In metallurgy, one of the most frequent wastes, known as scrap, is associated with material discarded due to process problems or inadequate quality of the manufactured products. Scrap in metallurgy can generate production losses that impact company costs, especially when the quality of products does not meet customer needs because they do not comply with consumer requirements (Li et al 2020;Petrov et al 2016;Vekovshinina et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When industrial objects including metallurgic and wood-processing enterprises are located within residential areas or close to them, it often results in poorer quality of ambient air and occurrence of related health disorders especially among children [1]. We ana-lyzed research works both by domestic and foreign researchers and revealed that it was not a rare case when the greatest part of a city population lived in zones exposed to chemical emissions and there were various negative responses regarding their health [2][3][4][5][6][7].…”
mentioning
confidence: 99%